2021
DOI: 10.1186/s12889-020-10139-z
|View full text |Cite
|
Sign up to set email alerts
|

Equity of expenditure changes associated with a sweetened-beverage tax in Tonga: repeated cross-sectional household surveys

Abstract: Background The aim of this study was to examine changes in beverage expenditure patterns before and after a T$0.50/L sweetened-beverage (SB) excise was introduced in Tonga in 2013, by household income, household age composition and island of residence. Methods Two cross-sectional surveys involved households being randomly sampled (the Household Income and Expenditure Surveys in 2009 (n = 1982) and 2015/16 (n = 1800)). Changes in soft drink (taxed),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…We found one difference in our analysis of bottled water purchasing, which suggested that lower-income households might be more likely to switch to bottled water than higher-income households in response to an SSB tax. This finding was similar to results based on a study of SSB and bottled water purchases in France [ 34 ] and in Tonga [ 35 ]. While it is possible that more households generally are purchasing bottled water over time, this result was specific to Philadelphia’s tax structure.…”
Section: Discussionsupporting
confidence: 91%
“…We found one difference in our analysis of bottled water purchasing, which suggested that lower-income households might be more likely to switch to bottled water than higher-income households in response to an SSB tax. This finding was similar to results based on a study of SSB and bottled water purchases in France [ 34 ] and in Tonga [ 35 ]. While it is possible that more households generally are purchasing bottled water over time, this result was specific to Philadelphia’s tax structure.…”
Section: Discussionsupporting
confidence: 91%
“…This also adds to the growing international evidence that SSB taxes may reduce inequalities in diet-related health outcomes. For example, some studies from other countries have shown that lower-income households were more likely to reduce their purchases or intake of sugar from SSBs following introduction of SSB taxes [ 36 , 50 , 51 ], although this is not always the case [ 22 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This also adds to the growing international evidence that SSB taxes may reduce inequalities in diet-related health outcomes. For example, some studies from other countries have shown that lower income households were more likely to reduce their purchases or intake of sugar from SSBs following introduction of SSB taxes [28,46,47] although this is not always the case [48][49][50].…”
Section: Comparison With Other Studies and Interpretation Of Resultsmentioning
confidence: 99%